Grenada : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Grenada. (IMF Staff Country Reports; Country Report ;, 2019)
Owing to improved policy frameworks and favorable external conditions, Grenada's economy has been growing rapidly. Policies have remained prudent, helping reduce public debt and financial system vulnerabilities. The domestic policy debate is increasingly focused on using potential fiscal space for spending on public pensions and investment on building resilience to natural disasters.